2011
DOI: 10.1021/ma200436w
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Yielding, Strain Softening, and Steady Plastic Flow in Polymer Glasses under Constant Strain Rate Deformation

Abstract: The nonlinear Langevin equation theory of segmental relaxation, elasticity, and nonlinear mechanical response of deformed polymer glasses with aging and mechanical rejuvenation processes taken into account is applied to study material response under a constant strain rate deformation. In the postyield softening regime, the amplitude of the stress overshoot feature, and its breadth in strain, are predicted to be positively correlated with the mechanically induced disordering process. The key physics is the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
130
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(163 citation statements)
references
References 66 publications
(177 reference statements)
24
130
0
1
Order By: Relevance
“…Mobility in the post-yield regime is found to be independent of previous aging time in the range of 0.5 to 1.5 hours. The postyield mobility is consistent with a linear dependence upon strain rate, although it is also consistent with the slightly sublinear dependence predicted by the theory of Chen and Schweizer 39 and observed in simulations by Riggleman et al 49 . These simulations 49 , the theory 39 , and our experiments agree that mobility is constant throughout the strain softening regime.…”
Section: Discussionsupporting
confidence: 89%
“…Mobility in the post-yield regime is found to be independent of previous aging time in the range of 0.5 to 1.5 hours. The postyield mobility is consistent with a linear dependence upon strain rate, although it is also consistent with the slightly sublinear dependence predicted by the theory of Chen and Schweizer 39 and observed in simulations by Riggleman et al 49 . These simulations 49 , the theory 39 , and our experiments agree that mobility is constant throughout the strain softening regime.…”
Section: Discussionsupporting
confidence: 89%
“…This previous work showed that small changes of the probe relaxation time in the post‐yield regime were due to small variations in the local strain rate and that correction for this effect yielded probe relaxation times that were constant in the post‐yield regime. The major features of the results are consistent with theory and simulations . At the lowest strain rate, the evolution of τ probe is not monotonic with strain; this is a reproducible feature of the data [see lowest strain rate data in Fig.…”
Section: Resultssupporting
confidence: 82%
“…Viewed from this perspective, the mechanical relaxation times must also show a large change in the pre‐yield regime that unfortunately was not observed in our experiments. The gradual shortening of the probe relaxation time observed here as yield is approached is qualitatively consistent with the behavior of the segmental relaxation time in computer simulations of polymer glasses and with the molecular theory of Chen and Schweizer . In contrast, the mechanical relaxation time approximately reaches its post‐yield value considerably before yield.…”
Section: Discussionsupporting
confidence: 87%
“…There seems to be general agreement between experiments, 21 theory, 9 and MD modeling 22−30 on the pivotal role of the amplitude of local density fluctuation, S 0 , as the primary structural variable in determining the deformation behavior of polymer glasses. The S 0 is related to the preparation protocol, thermodynamic, and loading conditions.…”
Section: ■ Introductionmentioning
confidence: 82%